KONSEP PEMBINAAN DAN PERTAHANAN KELUARGA DALAM PERSPEKTIF ISLAM - Nurdin Nurdin (State Islamic University (UIN) Ar-Raniry, 2019)
In essence, all people are able to carry out marriages, but the most difficult thing is to build and maintain a family that mawaddah warahmah. The reality now is that there is a lot of disharmony in the family, disputes, violence, and so on that it leads to divorce, this is inseparable from the lack of understanding of religion possessed by the family itself. This writing aims to reveal some of the concepts of coaching and family defense patterns with the patterns outlined in Islam. The technique used is content analysis which is an in-depth study of the contents of written or printed information in the media and other literatures whose sources are from the Koran, hadith, books, opinions of scholars. The data collection method is library research. The results of this study indicate that there is a lot of chaos and disputes within the household so that it leads to divorce because of the shallowness of religious values held by Muslims. Islam is a foothold or the main concept in fostering a complete family, because the concept it offers is the Qur'an and Sunnah that was once practiced by the Prophet in his life.